Prohibiting Television Advertising of Alcoholic Beverages : A Constitutional Analysis. (U.S. Congressional Research., 2002)
Discusses the Constitutionality of Congressional proposals to prohibit television and radio advertising of alcoholic beverages. Analyzes Supreme Court decisions involving the regulation of commercial speech and the recent decision by Distilled Spirits Council of the United States to lift the voluntary ban on advertisement of hard liquor.